Empowerment of social movements: alternative of warranty of human rights against citizenship as individualistic and excluding policy identity at the service of neoliberalism (2016)
Liberalism and neoliberalism entail, as a benchmark, two historic events of great value, the Declaration of Rights of Man and of the Citizen during the French Revolution, and the Universal Declaration of Human Rights of 1948, benchmarks of a new mode of social organization based not on rights but onmarketing strategies as an essential characteristic of neoliberalism, where citizenship entails the fulfillment of certain requirements typical of the reason, skin color (preferably white), religion, gender and property and its change until today is not significant, because although there are formal structures in the States, simulating the redefinition of the term, in practice it has not been reached, such as against the protection of the human right to health in States like Colombia, where the term is in the classification of the social security system, but does not exist yet in the realization of health services.